Crimes against humanity: A normative account - May, Larry (Cambridge University, 2013)
Crimes Against Humanity is the first booklength treatment of the philosophical foundations of international criminal law. Its focus is on the moral, legal, and political questions that arise when individuals who commit collective crimes, such as crimes against humanity, are held accountable by international criminal tribunals. These tribunals challenge one of the most sacred perogatives of states - sovereignty - breaches of which can be justified only in limited circumstances, following what the author calls a "minimalist account" of the justification of international prosecution." "Crimes Against Humanity will appeal to anyone with an interest in international law, political philosophy, international relations, and human rights theory.